2020
DOI: 10.1136/gutjnl-2019-320091
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic grading of gastric intestinal metaplasia on risk assessment for early gastric neoplasia: can we replace histology assessment also in the West?

Abstract: ObjectivesTo assess the value of endoscopic grading of gastric intestinal metaplasia (EGGIM), operative link on gastritis assessment (OLGA) and operative link on gastric intestinal metaplasia (OLGIM) on risk stratification for early gastric neoplasia (EGN) and to investigate other factors possibly associated with its development.DesignSingle centre, case–control study including 187 patients with EGN treated endoscopically and 187 age-matched and sex-matched control subjects. Individuals were classified accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 45 publications
0
44
0
2
Order By: Relevance
“…Based on the multifocal patterns of IM, an endoscopic mucosal examination of the entire stomach is recommended[ 47 ]. Marcos et al [ 48 ] reported that NBI endoscopic grading of IM was useful for risk assessment of early gastric neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the multifocal patterns of IM, an endoscopic mucosal examination of the entire stomach is recommended[ 47 ]. Marcos et al [ 48 ] reported that NBI endoscopic grading of IM was useful for risk assessment of early gastric neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment effect for poorly differentiated GC remains poor ( 33 , 61 ) and it has been demonstrated that poorly differentiated GC is a hotspot in clinical treatment research ( 35 ). GC is divided into early GC (stage I and II) and advanced GC (stage III or higher tumors) ( 36 38 ), and there are differences in treatment and surgical methods between early and advanced GC ( 39 , 40 ). Uzun et al ( 41 ) revealed that T1-T2 and T3-T4 classifications of patients with GC showed differences in their clinicopathological characteristics and survival status.…”
Section: Discussionmentioning
confidence: 99%
“…According to WHO's fifth edition of gastric cancer differentiation standard ( 32 ), the clinical characteristics and prognosis of patients with GC with well-moderately differentiated and patients with GC with poorly-signet differentiated were different ( 33 35 ), patients with GC with regards to histological grade were divided into the well-moderately group and poorly-signet group. According to the American Joint Committee on Cancer Staging System (8 th edition) ( 31 ), and the differences in treatment and surgical methods between early gastric cancer group (stage I and II) and advanced gastric cancer group (stage III or higher tumors) ( 36 40 ), patients with GC with regards to pathological stage were divided into the early GC group (stage I and II) and advanced GC group (stage III or higher tumors). According to the United States Joint Committee on Cancer Staging System (8 th edition) ( 31 ) and the differences between T3-T4 group and T1-T2 classification group with GC in chemotherapy and surgery ( 41 43 ), patients with GC in tumor (T) classification were divided into the T1-T2 and T3-T4 groups.…”
Section: Methodsmentioning
confidence: 99%
“…From February 2016 to November 2018, patients who were submitted to upper gastrointestinal endoscopy with high-definition virtual chromoendoscopy were prospectively screened for inclusion in this study. They were included if they could be classified in one of the 3 groups as follows: (A) controls with no/slight gastric atrophy or metaplasia (Operative Link for Gastritis Assessment [OLGA] stage 0-II and Operative Link for Gastric Intestinal Metaplasia [OLGIM] stage 0-II, and Endoscopic Grading of Gastric Intestinal Metaplasia [EGGIM] grade 0-4 [33][34][35]); (B) extensive atrophy/intestinal metaplasia (OLGA stage III-IV or OLGIM stage III-IV or EGGIM ≥ 5) and no history of gastric neoplasia; and (C) patients with EGN (visible lesion with dysplasia or early adenocarcinoma). Hp status was assessed by pathology analysis of antrum and corpus biopsy samples using the modified Giemsa stain.…”
Section: Patient Selection and Characteristicsmentioning
confidence: 99%